Sevoflurane Exerts Protective Effects in Murine Peritonitis-induced Sepsis via Hypoxia-inducible Factor 1α/Adenosine A2B Receptor Signaling - Ngamsri, Kristian-Christos; Fabian, Friederike; Fuhr, Anika; Gamper-Tsigaras, Jutta; Straub, Andreas; Fecher, David; Steinke, Maria; Walles, Heike; Reutershan, Jörg; Konrad, Franziska M. (Anesthesiology, 2021)
Background: Sepsis is one of the leading causes of mortality in intensive care units, and sedation in the intensive care unit during sepsis is usually performed intravenously. The inhalative anesthetic sevoflurane has been shown to elicit protective effects in various inflammatory studies, but its role in peritonitis-induced sepsis remains elusive. The hypothesis was that sevoflurane controls the neutrophil infiltration by stabilization of hypoxia-inducible factor 1α and elevated adenosine A2B receptor expression. Methods: In mouse models of zymosan- and fecal-induced peritonitis, male mice were anesthetized with sevoflurane (2 volume percent, 30 min) after the onset of inflammation. Control animals received the solvent saline. The neutrophil counts and adhesion molecules on neutrophils in the peritoneal lavage of wild-type, adenosine A2B receptor -/-, and chimeric animals were determined by flow cytometry 4 h after stimulation. Cytokines and protein release were determined in the lavage. Further, the adenosine A2B receptor and its transcription factor hypoxia-inducible factor 1α were evaluated by real-time polymerase chain reaction and Western blot analysis 4 h after stimulation. Results: Sevoflurane reduced the neutrophil counts in the peritoneal lavage (mean ± SD, 25 ± 17 × 105 vs. 12 ± 7 × 105 neutrophils; P = 0.004; n = 19/17) by lower expression of various adhesion molecules on neutrophils of wild-type animals but not of adenosine A2B receptor -/- animals. The cytokines concentration (means ± SD, tumor necrosis factor α [pg/ml], 523 ± 227 vs. 281 ± 101; P = 0.002; n = 9/9) and protein extravasation (mean ± SD [mg/ml], 1.4 ± 0.3 vs. 0.8 ± 0.4; P = 0.002; n = 12/11) were also lower after sevoflurane only in the wild-type mice. Chimeric mice showed the required expression of the adenosine A2B receptor on the hematopoietic and nonhematopoietic compartments for the protective effects of the anesthetic. Sevoflurane induced the expression of hypoxia-inducible factor 1α and adenosine A2B receptor in the intestine, liver, and lung. Conclusions: Sevoflurane exerts various protective effects in two murine peritonitis-induced sepsis models. These protective effects were linked with a functional adenosine A2B receptor.
CRIS-Team Scopus Importer:2022-11-17